Artificial infection with Fusarium solani f.sp. passiflorae in plants of passion fruit under controlled conditions - Martinez-Lemus, Erika Patricia; Osorio-Cardona, Jairo Antonio; Hio, Juan Climaco; Cruz-Castiblanco, Ginna Natalia; Aguirre-Rodríguez, Jaime Esneider; Rojas-Zambrano, Emerson Duvan; Vergara-Avila, Johan Andrés (Revista de Ciencias Agrícolas, 2023)
Controlled infection systems constitute a valuable tool in the study of pathosystems, as they enable the observation and measurement of specific characteristics with greater precision and ease compared to natural conditions. Additionally, they are useful for exploring and identifying sources of resistance in host populations. However, the plant's response to infection can vary depending on the inoculation method; invasive methods can damage plant parts, thus facilitating pathogen entry even in the presence of certain resistance mechanisms. The purpose of this study was to evaluate the reproducibility of an artificial infection protocol and an assessment scale for primary symptoms at the stem base/root collar, as well as secondary symptoms in leaves and roots of two Passiflora species. We evaluated the effects of inoculating planting substrates of sweet granadilla and purple passion fruit plants with three concentrations of F. solani f. sp. passiflorae (0.5 × 106, 1 × 106, and 2 × 106 conidia gram-1 of substrate), using non-inoculated plants as controls under controlled conditions. These treatments were tested in two separate experiments performed in 2017 and 2020. The study included symptom development readings integrated in a disease severity index (SI) for collar rot. Both experiments showed severity indices greater that 56%, indicating a high level of efficacy of the inoculation system for replicating disease symptoms in greenhouse settings. Our inoculation method reflects the conditions of natural infection of F. solani in sweet granadilla and purple passion fruit plants; it could be suitable for epidemiological and disease control studies, as well as for routine germplasm screening to identify sources of resistance.